John S. Anglin correspondence - Anglin, John S.
Correspondence.
In part, handwritten transcripts.
Confederate soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Soldiers -- Confederate States of America